32(460)"2004/...."
Contiene las conferencias de José Luis Rodríguez Zapatero, María Teresa Fernández de la Vega, Juan Carlos Rodríguez Ibarra, José María Barreda, Marcelino Iglesias, Jesús Caldera, Juan Fernando López Aguilar, José Blanco y Patxi López | 3 v."Edición con la colaboración de OHL"